Aplikasi Toko Online Berbasis Web Studi Kasus Pada Cilla Shop - Pitri; M. Syafiuddin Usman (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
Cilla shop stores that are engaged in sales, promotions and technology as well as waiters that make it easier for customers to make transactions can be a supporting factor in achieving sales success. In order to facilitate it all can be realized with an online store (E-Commerce). The built online store application aims to help the